Comparison of the Morse Fall Scale and STRATIFY scale on the risk of falls among the elderly - Assis Rodrigues, Josyenne; Moraes Penha, Ramon; Contrera, Luciana; Rosa Miziara Barbosa, Suzi; Anacleto Pinheiro, Edivania; de Lourdes Oshiro, Maria; Regina Martins Alvarenga, Márcia (O Mundo da Saúde, 2020)
The use of risk assessment instruments with an emphasis on preventing an event and reducing damage has provided support for the management of falls. The aim of the study was to perform a comparative analysis between the scales that predict falls among the elderly Morse Fall Scale (MFS) and St. Thomas Risk Assessment Tool in the Falling Elderly Inpatients (STRATIFY), in a unit of a philanthropic hospital, Campo Grande, MS, Brazil. A quantitative cross-sectional study was carried out from February to September 2018, by nurse residents in the Multiprofessional Health Residency Program, Campo Grande, MS. The STRATIFY and Morse Fall Scale instruments were used. The data were treated statistically by the Kolmogorov-Smirnov, Mann-Whitney U and Kruskal-wallis tests. 31 elderly people participated in the study. The results were heterogeneous in the comparison between the instruments, the MFS demonstrates that as the patient obtains mobility, the risk for falls increases; while STRATIFY, when investigating risk factors directed to the elderly, identified high levels of high risk for falls in the three assessment moments. It is concluded that the STRATIFY instrument was significantly associated with the risk of falling and had a better discrimination in predicting falls in hospitalized elderly than MFS.